Analysis of the management of business informatics framework from the green ICT viewpoint. (2016) - Buchalcevova, Alena
This paper concentrates on two key areas connected with business informatics, i.e., business informatics management and the role of ICT in promoting sustainable development. The surveys mentioned in this paper show that organisations in the Czech Republic do not devote sufficient attention to these areas and thus lag behind organisations in other developed countries. To help enterprises with the management of their business informatics, the management of business informatics (MBI) framework was developed. However, this framework does not explicitly address sustainable development or specifically green ICT. Therefore, the analysis of the MBI framework was carried out from the green ICT viewpoint to design the MBI framework extension towards green ICT adjustment.